EFFECOF EMPLOYMENT SUPERVISION AND EMPLOYEE SATISFACTION OF EMPLOYEE DISCIPLINE (EMPLOYEE CASE OF PTPN V UNIT TERANTAM) - ", Fratika; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The background of this research is that the organization can continuously improveits competitiveness. All that can be achieved if the employee is able to provide the bestperformance to achieve organizational goals. One of the employee's performance can beimproved through supervision in carrying out the work.               Supervision is a real and most effective action in realizing employee discipline. Job satisfaction affects the level of employee discipline, meaning that if there is satisfaction from work, then employee discipline is good. With the high discipline of each employee, the company will be able to operationalize all of its business strategies in order to achieve goals.               This research is a quantitative approach survey research. The sample of this research was the employees of PTPN V Kampar Terantam Unit, which numbered 90 employees with a sampling technique using the random sampling method. Data collection using questionnaires. Keywords: Job Supervision, Job Satisfaction, Work Discipline.